A novel clusterıng approach for vehıcular ad hoc network - Avcil, Muhammed Nur (My University, 2015)
Araçsal (Taşıtsal) Ağlar için Özgün Bir Kümeleme Yaklaşımı Kümeleme algoritmaları, çeşitli parçalara ayırma yöntemleri ile ağın yönetilebilmesini kolaylaştırmaktadır. Özellikle Araçsal ağlar (VANET) gibi bazı durumlarda kümeleme algoritmaları ile oldukça iyi performans gelişimi görülebilir, ancak ölçeklenebilirlik bakımından kümeleri birleştirme işlemi de ağ dengelilik özelliğini olumsuz yönde etkiler. Bu tezde, kümeleri birleştirmenin ağın dengesine etkilerini inceleyerek, elde edilen sonuçlara göre, yeni bir kümeleme algoritması, Yansız (Peşin Hükümsüz) Ortamlarda Göreceli Dengeli Kümeleme Algoritmasını (ReSCUE) öneriyoruz. ReSCUE’nun amacı ortam hakkında yanlı bir bilgi olmadan dengeli kümeler oluşturmaktır. ReSCUE algoritması, VANET araç karakteristiğinin zaman-mekan değişimlerini tutarak yerel alandaki bilgiler ile birlikte daha dengeli bir kümeleme yapmaktadır. ReSCUE algoritmasının performansını simülasyon ile değerlendirdiğimizde, kümelerin birleşmesinin engellenerek daha dengeli kümelerin oluşturulduğunu ve düğüm statü değişikliklerinin azaldığı görülmektedir.

A Novel Clustering Approach for Vehicular Ad Hoc Networks Clustering algorithms improve network manageability through several topology partitioning techniques. In some particular cases, such as vehicular ad hoc network (VANETs) communications, significant performance improvements can be introduced via clustered networking solutions whereas merging clusters for the sake of scalability may lead to degraded network stability. In this thesis, we explore the impact of merging clusters, and furthermore based on these results, we propose a new clustering technique, namely Relatively Stable Clustering for Unbiased Environments (ReSCUE). The objective of ReSCUE is primarily guaranteeing cluster stability in an unbiased manner. ReSCUE keeps track of the spatio-temporal changes in VANET node characteristics, and uses these characteristics along with local information to prevent biased clustering which is based on common and general node characteristics. We evaluate the performance of ReSCUE through simulations and show that ReSCUE can form relatively more stable clusters while reducing the frequency of cluster merges, as well as that of the node status changes.
Keywords: Ağlar; Bilgisayar Mühendisliği; Network